Intramolecular Singlet Fission in Acenes - Sanders, Samuel Nathan (2018)
In 2017, 98 gigawatts of solar capacity were added globally, outpacing new contributions from coal, gas and nuclear plants combined, based on 161 billion dollars of investment. Solar is the leading contributor to the clean energy revolution and continues to grow in market share and drop in price every year as economy of scale advances the technology. Within this market, silicon and cadmium telluride solar cells dominate nearly all of market share, converting roughly 20% of incident solar power into electricity. It is worth noting that the gains from a 1% increase in power conversion efficiency of the typical 20% solar cell to 21% would be measured, annually, in billions of dollars. If the solar cells installed last year had 1% more power conversion efficiency and the power displaced coal power generation, this enhancement in efficiency would now save roughly 8,000,000 pounds of carbon dioxide emission per hour every hour for the ~220,000-hour (~25 year) lifetime of the solar cells. Within this context, enhancing the power conversion efficiency of solar cells is crucial economically and environmentally. Because sunlight is incident on the earth as a broad spectrum of different colors, the energy of the photons spans a wide range. Unfortunately, the spectral range limits power conversion efficiency. For example, solar cells are transparent to photons with insufficient energy, while photons with excess energy relax to the band edge of the solar material, losing the excess energy as heat. This thesis focuses on improving the utilization of high energy photons currently lost to this thermalization process. In Chapter 1, we introduce the photophysical process of singlet exciton fission and give an overview of the field, with a focus on its potential for incorporation into photovoltaic devices. In Chapter 2-8, we discuss our results realizing singlet exciton fission in molecular systems, specifically bipentacenes. This chapter includes the synthesis of these materials, theoretical calculations predicting and rationalizing their photophysical behavior, and the spectroscopic characterization used to demonstrate the singlet fission process. In Chapter 3, we detail a modular synthetic approach to oligomers and even the first polymer of pentacene. We also discuss some basic properties of these materials using techniques such as linear absorption, cyclic voltammetry, and grazing incidence wide angle X-ray scattering spectroscopy. In Chapter 4, we investigate the photophysics of these materials. Photoluminescence upconversion spectroscopy reveals the decay of the singlet exciton on ultrafast timescales, while transient absorption spectroscopy is used to assign the singlet fission timescale, as well as to characterize the triplet absorption spectra. Chapter 5 discusses the synthesis and photophysics of homoconjugated and non-conjugated pentacene dimers, where singlet fission occurs through sigma bonds. Again, transient absorption spectroscopy is crucial to the assignment of the photophysics at play, but continuous wave time resolved electron spin resonance measurements yield additional insights into interaction between the resulting triplet pair excitons. Chapter 6 provides further detail into the formation of strongly exchange coupled triplet pair states. Continuous wave time resolved electron spin resonance spectroscopy is used to determine the quintet character of these states, and pulsed electron spin resonance measurements nutate the spin of these states to confirm this assignment. Chapter 7 provides the first demonstration that singlet exciton fission is also possible in heterodimer systems. Finally, Chapter 8 delves more deeply into the exciton correlations in these materials with a special focus on the pentacene-tetracene dimer system.